Premasticated food transfer by wild chimpanzee mothers with their infants: Effects of maternal parity, infant age and sex, and food properties. Issue 143 (June 2020) - Bădescu, Iulia; Sicotte, Pascale; Sandel, Aaron A.; Desruelle, Kelly J.; Curteanu, Cassandra; Watts, David P.; Sellen, Daniel W.
Abstract: Premasticated food transfer, when an individual partially breaks down food through chewing and feeds it to another individual, usually mouth-to-mouth, is described widely across human cultures. This behavior plays an important role in modern humans' strategy of complementary feeding, which involves supplementing maternal milk in infant diets with processed, easily digestible versions of adult foods. The extent to which other primates engage in premasticated food transfer with infants is unclear, as premasticated food transfers have been only occasionally reported in other ape species. We investigated premasticated food transfers in 62 mother-infant pairs of wild chimpanzees at Ngogo, Uganda, as well as unresisted food taking, when mothers passively allow infants to seize food. We evaluated the presence or absence and rates of premasticated food transfer and unresisted food taking relative to maternal parity and infant age and sex and assessed the food species and part used. We found that chimpanzee mothers regularly shared premasticated food with their infants aged between 6 months and 4 years, but they were more likely to share, and more frequently shared, with younger infants. The frequency with which females shared premasticated food may relate to maternal experience, as multiparous females shared premasticated food more often than did first-time mothers, which we did not find with unresisted food taking. Both easy-to-chew, commonly eaten foods and tougher, rarely eaten foods were shared. Premasticated food transfer and unresisted food taking may be infant-rearing strategies to facilitate the transition from a diet of exclusive maternal milk to solid food during early infancy. Premasticated food transfer in particular may provide energetic, immune, or growth benefits to infants through reduced chewing effort and maternal saliva. Given our findings in chimpanzees and earlier reports in other ape species, we suggest that the foundation of complementary feeding, a uniquely hominin strategy, might have been present in a common ancestor shared with the other great apes in the form of premasticated, mouth-to-mouth food transfer by mothers with their offspring.